2012
DOI: 10.21153/dpibe2012vol5no0art53
|View full text |Cite
|
Sign up to set email alerts
|

Does free trade result in higher GDP per capita: An International Perspective

Abstract: The theory of comparative advantage suggests that free trade increases overall world production of goods and services and it is a positive sum game in which all participating countries realise economic gains. The evaluation of data from a number of countries in this study demonstrates a strong correlation between a country's level of trade freedom (according to its Trade Freedom Index) and its GDP per capita. There are exceptions to this trend in countries that have experienced social or political unrest. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…This implies an increase in the value of Moroccan exports when it trades with countries of large economic size. This finding is perfectly in line with the results of Kee et al [46] and Lambrechts, Erin, and Rule [47] who provide strong evidence for a strong correlation between a country's trade volume and its GDP.…”
Section: Results Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This implies an increase in the value of Moroccan exports when it trades with countries of large economic size. This finding is perfectly in line with the results of Kee et al [46] and Lambrechts, Erin, and Rule [47] who provide strong evidence for a strong correlation between a country's trade volume and its GDP.…”
Section: Results Analysissupporting
confidence: 92%
“…The increase in the GDP in Africa influences positively the chances of trade with china;However, when there is a large gap between Morocco and its trading partners in terms of GDPper capita, it seems that the probability of trade decreases. This partly confirms the work of Lambrechts, Erin, and Rule [44] who suggests that there is a strong correlation between a country's level of trade freedom and its GDP per capita.…”
Section: Results Analysissupporting
confidence: 83%
“…This result does not confirm our initial hypothesis. However, it does validate the work of Lambrechts, McGrath, and Rule (2012) who state that other factors may also play a role in GDP growth and that when social unrest is evident, levels of trade freedom may not align with GDP growth. Economic growth and free trade cannot be measured in isolation to prove whether growth is improving or slowing.…”
Section: Interpretation Of the Resultsmentioning
confidence: 60%
“…The issue is complex and requires a thorough analysis of economic freedom factors encompassing business freedom, monetary freedom and property rights. Countries such as Argentina and Mexico have demonstrated that other factors can also affect GDP growth and that, when social unrest is evident, levels of trade freedom would not align with GDP growth (Lambrechts, McGrath, & Rule, 2012).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%